Updraft Downdraft: Secondary Schools In the Crosswinds of Reform - Crawford, Marilyn; Dougherty, Eleanor (Rowman & Littlefield Publishers, 2003)
Ever wonder why there is such a big gap in the number of students who succeed in comparison to those who do not? The duality of educational experiences that permeate our secondary schools leads to one group of students heading into post-secondary education, while others either receive terminal degrees or drop out. This updraft/downdraft phenomena occurs because time, talent, and monies tend to drift into the 'updraft' group's educational arena, leaving the 'downdraft' students and teachers with less time to teach, fewer qualified teachers, and fewer supporters. This book provides a set of tools to assist schools and communities in reallocating their resources more effectively. Using school 'artifacts,' educators can collect the data and information needed to make better decisions and leverage what they have, equitably. The process of collecting, analyzing, and acting on the data described promotes more strategic decision-making about school resources. Samples of data and analyses around master schedules, student schedules, curriculum guides and other 'artifacts' inside the school and district are provided. Recommended for anyone seeking ways to understand the problems inside the public schools and ways to find solutions.